Mobile banking: The impact of M-Pesa in Kenya - Isaac Mbiti; David N. Weil (Brown University, Department of Economics, 2011)
M-Pesa is a mobile phone based money transfer system in Kenya which grew at a blistering pace following its inception in 2007. We examine how M-Pesa is used as well as its economic impacts. Analyzing data from two waves of individual data on financial access in Kenya, we find that increased use of M-Pesa lowers the propensity of people to use informal savings mechanisms such as ROSCAS, but raises the probability of their being banked. Using aggregate data, we calculate the velocity of M-Pesa at between 11.0 and 14.6 person-to-person transfers per month. In addition, we find that M-Pesa causes decreases in the prices of competing money transfer services such as Western Union. While we find little evidence that people use their M-Pesa accounts as a place to store wealth, our results suggest that M-Pesa improves individual outcomes by promoting banking and increasing transfers.
Additional information: NBER Working Paper No. 17129.
Keywords: E40; O16; O33; 330